1998
DOI: 10.1074/jbc.273.51.34358
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, Organization, and Expression of α-Tubulin Genes in the Antarctic Fish Notothenia coriiceps

Abstract: To assess the organization and expression of tubulin genes in ectothermic vertebrates, we have chosen the Antarctic yellowbelly rockcod, Notothenia coriiceps, as a model system. The genome of N. coriiceps contains ϳ15 distinct DNA fragments complementary to ␣-tubulin cDNA probes, which suggests that the ␣-tubulins of this cold-adapted fish are encoded by a substantial multigene family. From an N. coriiceps testicular DNA library, we isolated a 13.8-kilobase pair genomic clone that contains a tightly linked clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…cDNA Library Construction and Screening-The production of two N. coriiceps brain cDNA libraries, the first primed with oligo(dT) and constructed in gt10 and the second primed with random hexanucleotides/oligo(dT) (75:25%) and cloned in ZAP II (Stratagene), has been described previously (13,14). The C. rastrospinosus brain cDNA library was constructed in gt10 by similar methods, with cDNA synthesis primed by a 50:50 mixture of random hexanucleotides and oligo(dT).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…cDNA Library Construction and Screening-The production of two N. coriiceps brain cDNA libraries, the first primed with oligo(dT) and constructed in gt10 and the second primed with random hexanucleotides/oligo(dT) (75:25%) and cloned in ZAP II (Stratagene), has been described previously (13,14). The C. rastrospinosus brain cDNA library was constructed in gt10 by similar methods, with cDNA synthesis primed by a 50:50 mixture of random hexanucleotides and oligo(dT).…”
Section: Methodsmentioning
confidence: 99%
“…Libraries were screened for recombinant clones containing ␣-and ␤-tubulin coding sequences as described by Parker and Detrich (14). One hundred fifty nine candidate ␣-tubulin cDNA isolates and 55 prospective ␤-tubulin cDNAs were obtained from a total of six screens of the two N. coriiceps libraries (632,000 total recombinant phage used in three ␣-screens, 385,000 for three ␤-screens).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychrophilic ciliates (Pucciarelli and Miceli, 2002) contain tubulin genes with relatively high A/T contents (α-55.7%, β-57.7%), which may facilitate DNA strand separation and favor DNA replication and transcription; similar observations have been made in other coldadapted taxa (e.g., Parker and Detrich, 1998;Zhao et al, 1998), but note that others have observed the opposite trend (e.g., Feller and Gerday, 2003). Ice worm tubulin genes were relatively G/C rich (i.e., ∼55%), which runs counter to other ice worms genes (e.g., ∼45% G/C content in a random sampling of ice worm genes; Farrell et al, 2004).…”
Section: Figmentioning
confidence: 73%
“…Posttranslational modifications such as polyglutamylation may also confer some cold stability to microtubules by reducing electrostatic repulsions between tubulin dimers (Redeker et al, 2004). Additionally, the presence of multigene tubulin families in N. coriiceps (nine α-and four β-isotypes) appears to facilitate the synthesis and maintenance of tubulin subunits at low physiological temperatures (Parker and Detrich, 1998).…”
Section: Introductionmentioning
confidence: 99%